2007
DOI: 10.1007/s10517-007-0202-z
|View full text |Cite
|
Sign up to set email alerts
|

Immunobiological specificity of antibodies against glutamate and γ-aminobutyric acid

Abstract: Experiments on C57Bl/6 mice showed that chronic epileptization of the brain (pharmacological pentylenetetrazole kindling) is accompanied by induction of autoantibodies against glutamate and GABA. Immunohistochemical similarity of antibodies against glutamate and GABA was demonstrated. Study on the model of pentylenetetrazole-induced acute generalized epileptiform activity showed high immunobiological specificity of intraperitoneally injected antibodies against GABA and glutamate: antiepileptic effect of antigl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…The possibility of Glu-Ab production was previously demonstrated [1,4,5]. We recently demonstrated the production of Glu-Ab in AD [2,3] and revealed peculiarities of Glu-Ab production in patients with various forms of AD.…”
mentioning
confidence: 76%
“…The possibility of Glu-Ab production was previously demonstrated [1,4,5]. We recently demonstrated the production of Glu-Ab in AD [2,3] and revealed peculiarities of Glu-Ab production in patients with various forms of AD.…”
mentioning
confidence: 76%
“…Glutamate (Glu) and GABA play a key role in central integration of HPA stress responses [11,12]. We previously showed the effects of antibodies (Ab) to Glu and GABA during active immunization with Glu-BSA and GABA-BSA conjugates on the development of convulsive reaction to pentilentetrazole, neurogenic pain syndrome, and combined water immersion stress [2,4,6]. A possible mechanism underlying the effect of Ab to neurotransmitters during active immunization is a direct infl uence on the brain Glu-and GABA-ergic systems.…”
mentioning
confidence: 99%
“…Previous studies revealed that antibodies to dopamine and serotonin play a role in immune modulation of brain functions that are related to the behavior and emotional state [2,6]. Antibodies to GLU and GABA had a modulatory effect on the symptoms of experimental epileptogenesis and central pain syndrome [1,3]. However, little is known about the influence of antibodies to GLU and GABA on the behavioral stress reaction in animals.…”
mentioning
confidence: 99%